New Technology in Automated Vehicles to Improve Passenger Safety - Suhardjono, Suhardjono; Priyono, Priyono; Sri Iswiyanti, Agus; Parulian, Dudi; Syah Putra, Arman; Aisyah, Nurul (CV. Inara, 2021)
The background of this research is by prioritizing how to improve the safety of passengers on a vehicle with increased security so that if an accident occurs, the passenger does not suffer any injury. If necessary, it is not scratched on the body. With this research, it is necessary to increase security in order to provide maximum protection. for passengers and motorists. The method used in this study using the literature review method based on research that has been done previously so that it can be the basis for this research. With the literature review, the research will be able to find new research problems so that this research can be the latest research in order to serve as the basis for future research. In this study, we will find out how to protect passengers on a vehicle with ways that passengers can do so that the security side can be improved. Therefore, the use of security in a vehicle is very important so that it can help drivers and passengers in driving. In this study will produce a proposed system that can be used as a basis as a guide in order to protect passengers and motorists and can improve the safety side of driving.